Strategi Menciptakan Iklim Kondusif di SD/MI (Sebuah Kajian Pedagogis Dan Psikologis) - Mustafida, Fita (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2016)
Student learning is closely related to the environment or atmosphere in which the process was ongoing. The joyful atmosphere brings excitement in learning. In contrast, tense, drab and less attractive atmosphere influences the student interest and enthusiasm. Teachers as the most responsible one for the classroom learning management are obliged to create a learning atmosphere that is convenient and fun for the children because the comfortable and enjoyable (conducive) classroom climate can enable them to transform interpersonal relationships so as to become a learning community that is productive and mutual respect, so enabling an effective learning interaction in nurturing the development of children or learners. Starting from this, the better classroom climate that is built, the better conditions of learning because only the conducive learning classroom atmosphere that is quiet, comfortable, fun, and full of significance can be realized.